On stochastic spatial patterns and neuronal polarity - Menchón, Silvia Adriana; Wio, Horacio Sergio (2022)
Fil: Menchón, Silvia Adriana. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.